The Declaration of His Majesty Sultan Qaboos: Towards a Harmonious Human Community - Zdanowski, Jerzy; Ziaka, Angeliki (Georg Olms Verlag, 2022)
The world needs a reasoned vision based on values that create new social awareness and promote harmony among humans. In 2018, Sultan Qaboos of Oman formulated the Declaration of the Harmonious Human Community in which people can nurture their sense of humanity and realize their aspirations for a world of peace, justice and progress. The contributors to this volume reflect on the Declaration and provide insights on Sultan Qaboos’s thinking from a mainly Muslim perspective. Agreeing on the ethical dimension of foreign policymaking, they challenge the dominant paradigm among Western scholars and strengthen constructivist thinking about international relations proposing that there is common ground for a global community based on shared norms and values.